Real time interpolation algorithm based on Lanczos kernel - Ying GUO; Lun LI; Peng WANG (Tongxin xuebao)
In order to improve the timeliness and reliability of color image scaling algorithms,a high effective real-time color image scaling algorithm was proposed,which first generated the kernel look up table that could be used for whole target image based on Lanczos kernel,and interpolation of all target image pixels had only fixed point operation which had low computational complexity.Meanwhile,an optimized method for rasterizing pixels of target image was proposed,which needed little memory space but embraced high efficiency of memory utilization.The experiment results show that the proposed algorithm achieves good image quality,and the computational complexity is far more less than classic image scaling algorithms.So the proposed algorithm can effectively implement real-time resizing of color images and color videos in any scaling factors.